Coronary reserve assessment with transthoracic Doppler echocardiography - V. V. Mazur; E. S. Mazur (Российский кардиологический журнал, 2005)
Using our original methodic of transthoracic Doppler assessment of coronary blood flow, we examined coronary resistance dynamics during physical stress tests in 12 patients with essential arterial hypertension (Group I), and 12 patients with effort angina (Group 2). In Group 1, physical exertion was associated with vascular resistance decrease in right coronary artery (RCA) basin by 66 %, comparing to baseline; in left coronary artery (LCA) basin - by 69 %. In Group 2, these figures were -58 % and +22 %, respectively. Coronary resistance increase among Group 2patients was associated with myocardial hypoand/or akinetic areas in LKA basin. The authors conclude that their methodic of transthoracic Doppler assessment of coronary blood flow enables clinicians to adequately evaluate coronary resistance dynamics during physical stress.